The Impact of Climate Change on the Agricultural Sector in Tempos Village, West Lombok - Jupri, Ahmad; Ahyadi, Hilman; Faudziah, Totum Aurora; Wulandari, Astri; Rabani, M. Restu; Lestari, Bening Sagita; Wijdan, Ifad; Apriadi, Rhandy Asmi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Climate change is a condition of climate elements whose intensity tends to change or deviate from average dynamics and conditions. Climate change is mainly caused by anthropogenic activities which produce greenhouse gas (GHG) emissions. This condition has an impact on the agricultural sector. This research aims to determine the impact of climate change on the agricultural sector by analyzing data obtained from the West Lombok Regency government and also comparing data from BPS with direct interviews with the farming community of Tempos Village to determine the effect of climate change on agricultural production in Tempos Village. The method used in this research is descriptive qualitative. The research results show that climate change in the context of temperature and rainfall parameters affects the agricultural sector in terms of plant growth and crop yields or agricultural production.